Analyze the Role of Employee Motivation in Improving Performance At PT. Sorby International Medan - Khairat, Aldi Fasta Bhiqul; Fahmi, Teuku; Zulkarnen, Zuliana; Taib, Zulkifli; Putra, Teguh Dwi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The role of work motivation in improving the performance of employees of PT. Sorby International Medan is the subject of this research.  This study uses a descriptive qualitative methodology that collects data through documentation, direct observation, and structured interviews. Information consisting of five purposively selected employees from different divisions. The research shows that work motivation, both intrinsic and extrinsic, influences worker performance. While extrinsic motivations such as compensation and incentives increase productivity, intrinsic motivation increases loyalty and morale. Improving overall performance fails due to an uneven reward system and a lack of attention to career development. This research found that motivation that is managed fairly and strategically can improve employee performance. This research suggests that companies create merit-based motivation systems, strengthen communication, and develop sustainable human resource development.